The Body Appreciation Scale-2: Item interpretation and sensitivity to priming. (March 2019) - Dignard, Nicole A.L.; Jarry, Josée L.
Highlights: Eight out of ten BAS-2 items were interpreted in terms of appearance. Measures administered prior to BAS-2 had no impact on item interpretation or scores. BAS-2 scores were lower when few or many items were interpreted in appearance terms. BAS-2 scores were negatively related to cognitive investment in appearance management. Abstract: The Body Appreciation Scale-2 (BAS-2) is a widely-used measure of positive body image. Items are worded ambiguously to allow reference to any aspect of the body during measure completion. We examined (a) how BAS-2 items are interpreted and whether this interpretation is influenced by the content of measures administered prior to it, (b) whether measures administered prior to the BAS-2 alter its scores or (c) the correlation between BAS-2 scores and scores on a measure of body dissatisfaction, (d) how BAS-2 item interpretation relates to total scores, and (e) whether BAS-2 scores are associated with investment in appearance for aesthetic purposes. Canadian female undergraduates ( N = 392) completed one of four priming questionnaires, followed by the BAS-2, and then indicated how they interpreted each BAS-2 item. Most items were interpreted in terms of appearance, with the primes having no impact on item interpretation, scores, or the magnitude of the correlation with body dissatisfaction. BAS-2 scores were highest among women interpreting a moderate number of items in terms of appearance and negatively correlated with investment for aesthetic purposes. Thus, the BAS-2 is not vulnerable to priming, but among young Western women, items are likely to be interpreted in terms of appearance.